1979
DOI: 10.1002/jcp.1041000202
|View full text |Cite
|
Sign up to set email alerts
|

α‐Amanitin and 5‐fluorouridine inhibition of serumstimulated DNA synthesis in quiescent AKR‐2B mouse embryo cells

Abstract: AKR-2B mouse embryo cells undergoing the serum-stimulated transition from a quiescent to a proliferating state exhibit an increase in the rate of hnRNA synthesis which appears to be mediated through an increase in the actual number of RNA polymerase II molecules. alpha-Amanitin, administered early in the prereplication interval following stimulation, effectively inhibits hnRNA synthesis, polysomal mRNA accumulation, polyribosome formation, and subsequent DNA synthesis, and cell division. Unexpectedly, alpha-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The previous data indicated that effects on early GO/Gl events might not be the primary mechanism for TGF,1 growth inhibition. Since traverse of the last half of Gi and commitment to DNA synthesis can occur in the absence of new RNA synthesis (34,35) (Table 1), and TGFfi1 can inhibit epithelial cell proliferation when added in late GI (Fig. 2) (10,15,27).…”
Section: Resultsmentioning
confidence: 99%
“…The previous data indicated that effects on early GO/Gl events might not be the primary mechanism for TGF,1 growth inhibition. Since traverse of the last half of Gi and commitment to DNA synthesis can occur in the absence of new RNA synthesis (34,35) (Table 1), and TGFfi1 can inhibit epithelial cell proliferation when added in late GI (Fig. 2) (10,15,27).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitor studies of i-free medium for quiescent, serum-starved murine AKR-2B cells have similarthen shifted into ly shown that hnRNA synthesis is required for entry into the in Fig. 7, 28% of S phase in the first few hours after serum stimulation, but not ilin entered the S in the last few hours (43). lls receiving 10% DRB is a relatively strong inhibitor of mRNA synthesis.…”
Section: Downloaded Frommentioning
confidence: 93%
“…1). Inhibitors of RNA synthesis can block this process, implying that the transcription of certain genes is required for a quiescent cell to reenter the cell cycle (2). The molecular mechanisms that regulate these genes are poorly understood but do not appear to involve the nuclear translocation of the hormone-receptor complex.…”
mentioning
confidence: 99%